(untitled) (Eurasian Journal of Philology Science and Education, 2019)
In this article, first, the political life of Wali Khan has been explained. Following on that, the letters have been analyzed from philological and lingustic perspectives, which he wrote to the Russian authorities in 1780s. This article was based on historical books from the Kazakh Han Sultanes and documents from Kazakh-Chinese-Manchu, in terms of language communication, by analyzing the historical texts in regards to Abilpeiz Wang. Meanwhile, it has been expounded that historical texts are not only a part of national culture, but also a source of information for the life of some historical figures. Meanwhile, some comparative study between the letters themselves and the translations in Russian has been made and some underlying mistakes have been corrected. In addition, these documents were reproduced first time by the origianl Arabic script, transcribed, and translated into the modern Kazakh actually so that the readers might understand easily.